The Impact of Social Media Marketing and Brand Awareness on Purchasing Decisions on Cosmetic Products - Cahyo Dinarso, Rahmat; Aprilia Nurhaliza, Dwi; Qomariah, Nurul (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Competition between whitening cosmetic products is increasing with the emergence of new products endorsed by artists. The first aim of this research is to find out and analyze the impact of social media marketing on purchasing decisions, the second aim is to find out and analyze the impact of brand awareness on purchasing decisions. All Scarlet cosmetics users at the Scarlet Fitriajaya Banyuwangi Outlet are the population in this study. A total of 180 respondents were sampled in this research. Validity tests and reliability tests were used in this research to test the research questionnaire. The research hypothesis developed needs to be tested using hypothesis testing. The research results show that social media marketing and brand awareness have a positive impact on purchasing decisions for scarlet cosmetic products.